(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This article presents psychological as well as organizational and managerial issues. The specified personality (temperament) concepts were interpreted with regard to the recruitment process of employees. An attempt was made to substantiate the thesis ac-cording to which certain personality (temperament) and characterological qualities have a significant influence on the proper selection of staff for specific positions in a company